A rare disease presenting with acute abdominal pain in a girl: Solitary cecal diverticulum - Özcan, Hakan; Özer, Mehmet; Kaya, Mete (The European Research Journal, 2025)
Solitary cecal diverticulum (SCD) is a rare gastrointestinal disease, especially in children, predominantly observed in middle-aged Asian men, and presented with nonspecific symptoms similar to acute appendicitis. Herein we report a case of SCD in a 15-year-old girl who had acute abdominal pain symptoms, and was diagnosed intraoperatively. The SCD, which contained a fecalith, was excised, followed by cecal repair and an appendectomy. Histopathological examination confirmed the diagnosis of SCD. This case highlights the importance of considering SCD in the differential diagnosis of acute abdominal pain, particularly in pediatric patients.